2008
DOI: 10.3208/sandf.48.155
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of Ageing Effects on the Elasto-Viscoplastic Behaviour of Geomaterial

Abstract: The time eŠects on the stress-strain behaviour of geomaterial consist of eŠects of loading rate and ageing. The positive ageing eŠects are analysed based on the results from drained triaxial compression (TC) tests on cement-mixed kaolin and well-graded gravelly soil and incorporated into a non-linear three-component model that can simulate the elasto-viscoplastic behaviour of geomaterials. The inviscid yielding is controlled by the inviscid yield stress that develops basically by irreversible straining and tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…It has been shown that, when the conˆning pressure isˆxed and only a single stress parameter is variable (e.g., the deviator stress or the principal stress ratio), this model can accurately simulate elasto-viscoplastic behaviour of a wide variety of geomaterials not exhibiting ageing eŠects during and after complex and arbitrary loading histories (Tatsuoka et al, , 2008aDi Benedetto et al, 2002;Kongkitkul et al, 2008). Moreover, the model can easily incorporate ageing eŠects via those on elastic and plastic components (Tatsuoka et al, 2008b(Tatsuoka et al, , 2008c. The model is only brie‰y described below, as its detailed description under general stress conditions is not the primary purpose of this paper.…”
Section: Non Linear Three-component Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been shown that, when the conˆning pressure isˆxed and only a single stress parameter is variable (e.g., the deviator stress or the principal stress ratio), this model can accurately simulate elasto-viscoplastic behaviour of a wide variety of geomaterials not exhibiting ageing eŠects during and after complex and arbitrary loading histories (Tatsuoka et al, , 2008aDi Benedetto et al, 2002;Kongkitkul et al, 2008). Moreover, the model can easily incorporate ageing eŠects via those on elastic and plastic components (Tatsuoka et al, 2008b(Tatsuoka et al, , 2008c. The model is only brie‰y described below, as its detailed description under general stress conditions is not the primary purpose of this paper.…”
Section: Non Linear Three-component Modelmentioning
confidence: 99%
“…On the other hand, to describe the other viscous property types (i.e., TESRA, Combined and P and N), eŠects of previous loading history need to be taken into account by introducing the decay function gdecay, which is a function of the current irreversible strain and a strain history parameter controlling the decay rate, as described in details by Di and Tatsuoka et al (2002Tatsuoka et al ( , 2008a. The previous studies Tatsuoka et al, 2008b) showed that the viscous property of the cement-mixed gravelly soil used in the present study is the Isotach type in the pre-peak regime while it changes toward the TESRA type in the postpeak regime. In the following part of this paper, as only the yielding characteristics of cement-mixed GM in the pre-peak regime is analyzed, only the Isotach type viscous property is dealt with.…”
Section: Non Linear Three-component Modelmentioning
confidence: 99%
See 3 more Smart Citations